A Study of the chemical nature of sulfur-containing rocks and Frasch sulfur in the Al-Mishraq Sulfur field - Hala Jasim; thaer halo; Motea Al jbouri (College of Education for Pure Sciences, 2021)
The economic evaluation of the exploration sulfur well depends mainly on the elemental sulfur content and its association other factors, so a sample of sulfur rocks extracted by a special excavator for one of the exploratory wells was studied and in the form of a bore hole rock. The elemental sulfur ratio reached 12.8% an important ratio in estimating the explored sulfur reserves and through XRD, the predominant crystalline composition is calcite mineral with hexagonal crystalline form and with a lesser percentage in orthorhombic crystal sulfur this supports one of the theories that explained the formation of sulfur. Also, the mine Mishraq sulfur extracted by the underground melting method (known as the Frasch process) was studied chemically, and the elemental sulfur ratio reached 98.58% and the bituminous material 1.157%. Also, the SEM scanning electron microscope showed the presence of nanotubes of size (20-44 nm) belonging to the carb-sulfur compounds in the SEM, which are observed for the first time in this form.